Authority and Accuracy: A Study on LPMQ’s Role in Regulating Digital Translations of The Qur’an - Alauddin, Faiz; Taufiq, Mirwan Akhmad (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
This study investigates the diverse formats and categories of publications available for digital translations of the Holy Quran. Given the Quran's significance in Islam, its translation into various languages is vital for non-Arabic-speaking Muslims and scholars worldwide. The research delves into traditional printed translations, such as pocket sized editions, comprehensive annotated versions, and parallel text formats, comparing them to digital translations available in e-books, mobile applications, and online platforms. The study also examines the unique challenges posed by translating the Quran, including the preservation of its linguistic and theological nuances in different languages and mediums. By analyzing these aspects, the paper aims to shed light on the evolving methods of disseminating Quranic translations, emphasizing the balance between accessibility and the faithful representation of the sacred text. In this modern era, we cannot deny that the development of electronics is rapidly increase and has an impact on social life, even in this modern era we can get everything easily, including the model and type of digital Qur'an translation publications in the 5.0 era, this phenomenon raises several questions regarding the validity of the translation in the digital Qur'an model, is it in accordance with the provisions of the Indonesian LPMQ (Lajnah Pentashihan Mushaf al-Qur’an)? How does the birth of the digital Qur'an form of expression affect the study of the Qur'an in Indonesia? This article argues that these Qur'ans express interactivity in religion. The study of the model and type of Qur'an translation publications in this digital era aims to test the validity of the Qur'an translation.